1958
DOI: 10.1039/tf9585400381
|View full text |Cite
|
Sign up to set email alerts
|

The pyrolysis of chlorobenzene

Abstract: A study of the thermal decomposition of chlorobenzene shows that two quite distinct mechanisms can operate according to the temperature. Between 770 and 800" C, the main products are hydrogen chloride, hydrogen and p : p'-dichlorodiphenyl ; chlorine atoms and chlorophenyl radicals appear to be the principal carriers involved in a chain cycle in which there is little or no rupture of the aromatic ring. At higher temperatures (800-850" C), extensive ring-breaking occurs and quite large yields of vinyl chloride a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Cullis and Manton [24] found that the addition of hydrogen accelerated the decomposition of chlorobenzene. Louw et al [6] postulated that using H2 in excess would lead to a dechlorination of chlorinated aromatic compounds.…”
Section: Effect Of Two Hydrogen Donors: H2 and Methane (Jsr)mentioning
confidence: 99%
“…Cullis and Manton [24] found that the addition of hydrogen accelerated the decomposition of chlorobenzene. Louw et al [6] postulated that using H2 in excess would lead to a dechlorination of chlorinated aromatic compounds.…”
Section: Effect Of Two Hydrogen Donors: H2 and Methane (Jsr)mentioning
confidence: 99%
“…When the temperature is raised up to 550 °C, the concentration of chlorobenzene in the outlet stream is similar to that at 500 °C. Cullis et al 26 reported a minimum thermal decomposition temperature of 740 °C for chlorobenzene, mainly via stripping of the aromatic rings forming benzene. Li et al 27 reported that chlorobenzene does not undergo decomposition below 600 °C in an inert gas, but there is a small extent of decomposition in hydrogen at 500 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%